Dynamics of body weight and comorbidities in obese patients after sleeve gastrectomy vs. gastric bypass - Anna R. Volkova; Michael B. Fishman; Galina V. Semikova (Эндокринная хирургия, 2020)
Background: Bariatric surgery methods have proven to be most effective in treating obesity. Weight regain (WR) is often found after various types of bariatric surgery. The clinical significance of WR is not clearly defined.